2018
DOI: 10.1088/1361-6528/aaae53
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heating parameters on sintering behaviors and properties of mullite whisker frameworks

Abstract: Mullite whisker frameworks were fabricated by vapor-solid reaction with SiO2, Al2O3 and AlF3 powders as the whisker forming agent at high temperatures. The effects of heating temperature and soaking time on the weight loss, liner shrinkage, porosity, microstructure and compressive strength were investigated. The results showed that with the increasing of the sintering temperature and soaking time, the weight loss and liner shrinkage of the samples increased and the porosities decreased due to the accelerated v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…To date, it is known that mullite whisker, TiCN whisker and SiC whisker etc. have been successfully synthesized and potentially used as the reinforcing and toughening phases in the ceramic-based composites, diesel particulate filters, catalytic supporters and drug delivers [5][6][7][8][9][10][11][12][13][14]. For example, Z. Zhao et al fabricated 15 vol.% TiC 0.3 N 0.7 whisker reinforced β-sialon composite at 1750 • C under 30 MPa and confirmed that the hardness and fracture toughness were effectively improved [11].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…To date, it is known that mullite whisker, TiCN whisker and SiC whisker etc. have been successfully synthesized and potentially used as the reinforcing and toughening phases in the ceramic-based composites, diesel particulate filters, catalytic supporters and drug delivers [5][6][7][8][9][10][11][12][13][14]. For example, Z. Zhao et al fabricated 15 vol.% TiC 0.3 N 0.7 whisker reinforced β-sialon composite at 1750 • C under 30 MPa and confirmed that the hardness and fracture toughness were effectively improved [11].…”
Section: Introductionmentioning
confidence: 94%
“…Y.M. Zhang et al have prepared mullite frameworks using vapor-solid reaction with SiO 2 , Al 2 O 3 and AlF 3 as the forming agent at 1500 • C and determined that the framework possessed high porosity of 62.3% and high compressive strength of 142 MPa [14].…”
Section: Introductionmentioning
confidence: 99%